Penerapan Prinsip Good Governance dalam Program Makan Bergizi Gratis di SMP Negeri 13 Surabaya - Wardani, Afifah Layla; Yuliani Natalia; Yasmin Eka Febrianti; Millensyah, Erwing Wahyu (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
The Free Nutritious Meal Program (MBG) is a national priority program aimed at improving students’ nutritional status as part of efforts to enhance the quality of human resources. The success of this program is determined not only by nutritional fulfillment but also by the quality of governance in its implementation. This study aims to analyze the application of Good Governance principles in the Free Nutritious Meal Program at SMP Negeri 13 Surabaya. A qualitative method with a case study approach was employed. Data were collected through observation, interviews, documentation, and document analysis involving students, parents, teachers, and personnel from the Jemur Wonosari 1 Nutrition Program Service Unit (SPPG). Data were analyzed using the Miles and Huberman interactive model, consisting of data condensation, data display, and conclusion drawing. The findings indicate that the implementation of the Free Nutritious Meal Program has reflected most Good Governance principles, particularly in terms of regulatory compliance, equitable service access, implementation effectiveness, and stakeholder coordination. However, improvements are still needed in beneficiary participation, information transparency, evaluation mechanisms, and program feedback systems. These findings provide important implications for strengthening the governance of the Free Nutritious Meal Program to become more participatory, transparent, accountable, and sustainable.